Tutankhamun's trumpet : ancient Egypt in 100 objects from the boy king's tomb - Wilkinson, Toby, 1969- (W.W. Norton & Company, 2023)
"Marking the 100th anniversary of the discovery of Tutankhamun's spectacular tomb, its incredible treasures are revealed as never before. In 1922, after fifteen years of searching, archaeologists finally discovered the tomb of King Tutankhamun. There, buried alongside the king's mummy, they found more than 5,000 unique objects, each with a story to tell about ancient life. Tutankhamun's spectacular gold mask is justifiably famous, but the rest of the treasures remain largely unknown. In this rich and beautifully illustrated work of history, renowned Egyptologist Toby Wilkinson examines a civilization through the lens of the objects it most prized, from the precious (a ceremonial sickle, an ostrich-feather fan, a gold-decorated chariot) to the everyday (shaving equipment, a first-aid kit, loaves of bread). And perhaps most poignant of all the objects in the tomb is one that conjures up a lost world of human experience: Tutankhamun's silver trumpet. Wilkinson tells the stories of 100 such artifacts, creating an indelible portrait not just of Tutankhamun, but of the history, culture, and people of Ancient Egypt"--